Analisis Manajemen Laba Terhadap Laporan Keuangan - Sri Bulkia; Junaidi Junaidi; Periyadi Periyadi (STIKes Ibnu Sina Ajibarang, 2024)
Abstract. The purpose of the financial reporting system described above refers to conventional BTN financial reports as a whole because the financial reports at BTN Syariah KCS Banjarmasin still return to their parent bank where all BTN Syariah throughout Indonesia are business units of BTN Conventional. The research method in this study was carried out qualitatively with a descriptive approach. This research data uses primary and secondary data. Data collection techniques use observation and interviews. Meanwhile, research techniques use data presentation and drawing conclusions. Based on the results of the research, it shows that the processing of earnings management at BTN Syariah KCS Banjarmasin is quite efficient due to good working capital turnover as a means of generating profits. Judging from the net profit margin, it is quite efficient with an average percentage of 78.02%. The rate of return on assets is also efficient, although it continues to decline with a percentage of 1.41% and the rate of return on capital is considered effective with an average percentage of 13.15%. The author provides input to the bank so that the management of the financial reporting system at BTN KCS Banjarmasin is managed by the bank at each branch office or unit so that each financial report and profit management at the bank is more specific. Islamic banking academics should always participate in the development of sharia banking by providing input to financial institutions and also providing understanding to the public so they can differentiate between the bank interest system and the profit sharing system in banking. And also provide knowledge so that people do not get involved in the practice of interest which can actually lead to usury.